Entrepreneurial Finance and Nondiversifiable Risk - Chen, Hui; Miao, Jianjun; Wang, Neng (Review of Financial Studies, 2010)
We develop a dynamic incomplete-markets model of entrepreneurial firms, and demonstrate the implications of nondiversifiable risks for entrepreneurs' interdependent consumption, portfolio allocation, financing, investment, and business exit decisions. We characterize the optimal capital structure via a generalized tradeoff model where risky debt provides significant diversification benefits. Nondiversifiable risks have several important implications: More risk-averse entrepreneurs default earlier, but choose higher leverage; lack of diversification causes entrepreneurial firms to underinvest relative to public firms, and risky debt partially alleviates this problem; and entrepreneurial risk aversion can overturn the risk-shifting incentives induced by risky debt. We also analytically characterize the idiosyncratic risk premium.